THE ROLE OF MANAGERIAL LEADERSHIP IN THE SERVICE TRANSFORMATION OF SARI RASA HOTEL, WEST LAMPUNG REGENCY - Denny Permadi; Agus Purnomo (International Journal of Multidisciplinary Reseach, 2026)
The research method used was descriptive qualitative research. This method was used to describe the role of managerial leadership in the service transformation of the Sari Rasa Hotel in West Lampung Regency. All data were obtained directly from informants in the field using interviews and document studies. The results of the study indicate the role of managerial leadership in the service transformation at the Sari Rasa Hotel in West Lampung Regency. Based on the results, it was concluded that: (1) Idealized Influence: Managerial leadership has acted as a guiding figure in service change; (2) Inspirational Motivation: Leadership has attempted to encourage service transformation through work direction. (3) Individualized Consideration: Leadership attention to the needs and development of individual employees is present. (4) High Performance Expectation/Supportive Leader Behavior: Leadership sets high service performance standards.